One Word that will change your life - Britton, Dan (John Wiley & Sons, 2013)
IOne Word/iis a simple concept that delivers powerful life change! In 1999, the authors discovered a better way tobecome their best and live a life of impact. Instead of creating endless goals and resolutions, they found one word that would be their driving force for the year. No goals. No wish lists. Just one word. Best of all ... anyone, anytime can discover their word for the year./ iOne Wordthat will Change Your Life/iwill inspire you to simplify your life and work by focusing on justone wordfor this year. That's right!iOneWord/icreates clarity, power, passion and life-change. The simple power of One Word is that it impacts all six dimensions of your life ' mental, physical, emotional, relational, spiritual, and financial. Simply put, iOne Word/isticks. There is a word meant for you and when you find it, live it, and share it, your life will become more rewarding and exciting than ever./ Join thousands of people and hundreds of schools, businesses, churches, and sports teams who have found theirone word. . . and discover how to harness the transformational power ofiOne Word/i./ The book includes a personal Action Plan and simple process to help you discover your word for the year.
Print version record
Keywords: Self-actualization (Psychology) -- Religious aspects -- Christianity; Self-actualization (Psychology); Motivation (Psychology) -- Religious aspects; Motivation (Psychology); Christian life; Commitment (Psychology); Motivation; Motivation (Psychologie); Aspect religieux; Motivation (Psychologie); Vie chrétienne; Engagement; BUSINESS & ECONOMICS; Motivational; Motivation (Psychology); Religious aspects; Self-actualization (Psychology); Religious aspects; Christianity